Respuesta :
To solve this problem, there is a very simple trick, once you see it. The first step is to subtract the second equation from the first equation. This gives:
6x + 6y = 60
Multiply by 5/3 to get 10x + 10y
10x + 10y = 60 * 5/3
10x + 10y = 100
6x + 6y = 60
Multiply by 5/3 to get 10x + 10y
10x + 10y = 60 * 5/3
10x + 10y = 100
Hello !
5x² + 6x = 70
5x² - 6y = 10
We can reduce 5x² by decreasing the second ecuation so:
5x² + 6x - (5x² - 6y) = 70 - 10
5x² + 6x - 5x² +6y = 60
6x + 6y = 60
Now we can divide by 6 and eliminate it too :
x+y = 10
Multiplying by 10,we'll have :
10x+10y = 10*10 = 100
5x² + 6x = 70
5x² - 6y = 10
We can reduce 5x² by decreasing the second ecuation so:
5x² + 6x - (5x² - 6y) = 70 - 10
5x² + 6x - 5x² +6y = 60
6x + 6y = 60
Now we can divide by 6 and eliminate it too :
x+y = 10
Multiplying by 10,we'll have :
10x+10y = 10*10 = 100